An ultrasensitive scanning electrochemical microscopy (SECM)-based DNA biosensing platform amplified with the long self-assembled DNA concatemers. (20th February 2016) - Chen, Baoping; Hu, Qingqing; Xiong, Qiang; Zhang, Fan; He, Pingang
Abstract: The long DNA concatemers have been well developed to fabricate various biosensing platforms for the signal amplification. Herein, this signal amplification strategy was firstly used for an ultrasensitive scanning electrochemical microscopy (SECM)-based DNA biosensing platform. This platform was constructed through the hybridization of target DNA (TD) with thiol-tethered DNA capture probes (CP), immobilized on the gold substrate surface, and biotinylated DNA signal probes (SP), which formed then the long DNA concatemers through the continuous self-assembly with alternating DNA auxiliary probes (AP). The streptavidin-horseradish peroxidase (HRP) was linked to the long DNA concatemers through biotin-streptavidin interaction. In the HRP-catalyzed reaction, hydroquinone (H2 Q) was oxidized to benzoquinone (BQ) with H2 O2 at the modified substrate surface where sequence-specific hybridization had occurred, and the BQ generated could be monitored by a SECM tip. This platform exhibited a low detection limit of 0.18 aM estimated by the 3σ rule. Combined with DNA microarrays, four kinds of TDs (100 fM) as the models were detected simultaneously by using this proposed strategy, which also demonstrated sufficient selectivity to distinguish specific DNA sequences and good reproducibility. This method opens a promising direction to improve the SECM sensitivity for high-throughput DNA detection.